Magnetostratigraphic and chronostratigraphic constraints on the Marathousa 1 Lower Palaeolithic site and the Middle Pleistocene deposits of the Megalopolis basin, Greece. (20th December 2018) - Tourloukis, Vangelis; Muttoni, Giovanni; Karkanas, Panagiotis; Monesi, Edoardo; Scardia, Giancarlo; Panagopoulou, Eleni; Harvati, Katerina
Abstract: We investigated the magnetostratigraphy of the Megalopolis basin in central Peloponnese, Greece, which encompasses a record of Pleistocene lacustrine and lignite-bearing sedimentation, where lithic tools stratigraphically associated with remnants of an almost complete skeleton of Palaeoloxodon antiquus were recently found at the Marathousa 1 site. A magnetic polarity reversal was observed within a ∼10 m-thick lignite seam at the base of the (exposed) stratigraphic sequence, and it was interpreted as a record of the Brunhes/Matuyama boundary (0.78 Ma). Assuming that lignite seams were deposited generally under warm and humid climate conditions, this finding is in agreement with data from the literature indicating that the Brunhes/Matuyama boundary occurs within warm Marine Isotope Stage (MIS) 19. We then attempted to correlate the remainder of the lacustrine and lignite-bearing intervals above the Brunhes/Matuyama boundary to a standard oxygen isotope record of Pleistocene climate variability. Two age models of sedimentation were generated: according to preferred option #1, the artifact-bearing stratigraphic units of the Marathousa 1 site should have an age between ∼0.48 Ma and ∼0.42 Ma, while according to alternative option #2, the archaeological layers would have an age between ∼0.56 Ma and ∼0.54 Ma. Option #1 is at present considered the preferred option as it is in closer agreement with preliminary post-IR IRSL and ESR dates from the Marathousa 1 site. This age model has been exported to other areas of the Megalopolis basin, where additional archaeological and/or palaeontological sites could be present, by means of correlations to lithostratigraphic logs derived from commercial drill cores taken in the 1960s and 1970s for lignite exploitation.